(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2024)
The flood of resumes in today’s talent acquisition landscape makes it difficult for hiring managers and recruiters to find qualified applicants quickly. This study presents an innovative method to integrate artificial intelligence techniques into a custom application to expedite the resume screening process. The program increases the effectiveness of recruitment workflows by a webapp that can be created to take inputs in form of pdf or csv format from the user and screens the resume. The development of a prototype application is the first step in the research methodology. It is then thoroughly verified and analyzed.